Smart Detector System for Landslide and Soil Movement Using Internet of Things - Muhammad Sufian; Mohd Hakimi Zohari (Progress in Engineering Application and Technology, 2025)
The purpose of this study is to develop a Smart Detector System for Landslide and Soil Movement using IoT technologies to address the limitations of traditional landslide monitoring methods. The system focuses on providing real-time monitoring, early detection, and timely alerts to minimize risks to life, property, and infrastructure in landslide-prone areas. By incorporating advanced sensor networks, such as vibration sensors, and soil moisture sensors, the system continuously monitors raw data environmental factors. Data from these sensors are transmitted to a centralized platform for real-time analysis, leveraging machine learning techniques to detect early signs of potential landslides. This project is built to be flexible, affordable, and easy to use in different locations, making it suitable for many landslide-prone areas. It is expected to improve how quickly and accurately landslides can be detected, while also providing constant monitoring of soil and environmental changes. By using advanced technology and data analysis, the system aims to protect communities and buildings by reducing the dangers and damage caused by landslides, helping these areas become safer and more prepared.